Conflict, civil society, and women's empowerment : insights from the West Bank and the Gaza Strip - Natil, Ibrahim (Emerald points., 2021)
Conflict, Civil Society, and Women's Empowerment: Insights from the West Bank and the Gaza Stripis a specific study on how civil society organizations (CSOs) foster civic engagement, resilience and women's empowerment in the Gaza Strip and the West Bank.